2018
DOI: 10.1121/1.5024235
|View full text |Cite
|
Sign up to set email alerts
|

Progressive phase trends in plates with embedded acoustic black holes

Abstract: Acoustic black holes (ABHs) have been explored and demonstrated to be effective passive treatments for broadband noise and vibration control. Performance metrics for assessing damping concepts are often focused on maximizing structural damping loss factors. Optimally performing damping treatments can reduce the resonant response of a driven system well below the direct field response. This results in a finite structure whose vibration input-output response follows that of an infinite structure. The vibration m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…However, there is also a known drawback regarding the ABH strategy: namely, it is generally inefficient in the low-frequency range [5,23]. In some recent contributions, it has been rigorously demonstrated that a cut-on frequency exists, below which the ABH may lose its effectiveness [24,25]. Although in the aforementioned linear ABH structures, the cuton frequency could be somehow reduced through certain optimizations, it is unfortunately unavoidable in any implementation.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is also a known drawback regarding the ABH strategy: namely, it is generally inefficient in the low-frequency range [5,23]. In some recent contributions, it has been rigorously demonstrated that a cut-on frequency exists, below which the ABH may lose its effectiveness [24,25]. Although in the aforementioned linear ABH structures, the cuton frequency could be somehow reduced through certain optimizations, it is unfortunately unavoidable in any implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao [42] 提出声学黑洞与夹层板相结合的复 合结构, 研究表明, 该结构在低频段具有高效的减振性能. Conlon 和 Feurtado [43] 3.2 波动调控 声学黑洞的波动调控主要在二维薄板上展开, 因此二维圆形声学黑洞中的弯曲波聚焦和透镜效应是基于径向 弯曲波波速下降的物理原理. 数值研究 [44] 表明, 通过使用线源在嵌入二维圆形声学黑洞的平板中激发兰姆波, 实 验证明了透镜效应和聚焦效应 [45] .…”
Section: 减振unclassified
“…Although the ABH effect leads to very attractive damping efficiency in the mid to high frequency ranges -beyond a so-called cut-on frequency -, its damping capacity in the low-frequency range remains limited. Different analyses of the cut-on frequency have been pointed out, based on geometrical considerations [13,14], following a phase point of view [15], from the analysis of dispersion relations [16], or in terms of localized modes [17]. In any case, the cut-on frequency represents the threshold frequency under which all the usual designs of ABH working on their linear regime do not lead to damping properties, due to the large typical wavelengths compared with the ABH characteristic length.…”
Section: Introductionmentioning
confidence: 99%